Analysis of Injectable Contraceptive Use and Hypertension Incidence (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Background Injectable contraception is one of the family planning methods widely used by women of reproductive age in Indonesia due to its effectiveness and convenience. However, long-term use of hormonal contraceptives can cause side effects, one of which is increased blood pressure. Research Objective This study aims to examine how injectable contraceptives affect the incidence of hypertension in women of reproductive age. Research Method was conducted with an analytical design using simple random sampling technique at Dahlia Health Center Makassar in 2024. Research Results showed that from 40 respondents, 1-month injectable contraceptive acceptors consisted of 17 people who did not experience hypertension and 1 person who experienced hypertension totaling 18 people (45%), while 3-month injectable contraceptive acceptors consisted of 19 people who experienced hypertension and 3 people who did not have hypertension totaling 22 people (55%). This means more people experienced hypertension in 3-month injectable contraceptive acceptors compared to 1-month. Conclusion Fisher test results showed a significant value < 0.05, indicating a very strong relationship between contraceptive type and hypertension incidence. The 3-month injectable contraceptive type (containing high-dose progestin such as DMPA) is more likely to cause side effects in the form of increased blood pressure compared to 1-month injectable contraceptives which usually contain estrogen-progestin combinations in lower doses. Recommendations include the need for regular blood pressure monitoring in injectable contraceptive users, especially 3-month injections. Appropriate education from health personnel regarding risks and selection of contraceptive methods according to individual medical conditions as well as consideration of using non-hormonal contraceptives for women with a history of hypertension or cardiovascular disease risk.